Influence of Visual Quality and Cultural Background on Consumer Apple Preferences: An Eye-Tracking Study with Chinese and Hungarian Consumers - Xu Cao; Zsuzsanna Horváth-Mezőfi; Zoltán Sasvár; Gergő Szabó; Attila Gere; Géza Hitka; Dalma Radványi (Applied Sciences)
Using eye-tracking technology, the proposed study investigates how customers visually evaluate apples varieties and apple defects and how these evaluations affect their purchasing decisions. Three aspects were examined in this study: apple variety, defect severity, and cultural background. Idared, Golden Delicious Yellow, and Golden Delicious Green apple varieties with increasing degrees of bruising were shown to Chinese and Hungarian participants. The findings show that apple variety had no significant effect on gaze patterns, whereas cultural background had a considerable impact on visual attention measures. The most important element in grabbing and retaining customer attention was the severity of the defect, which was measured by area. The “Threshold of Rejection”, which characterizes consumer tolerance for Apple defects, is introduced in the study. Furthermore, a polynomial regression model was created to predict the probability of repurchasing an apple depending on its visual quality (level of bruising). These results provide useful information for marketing plans, quality assurance, and comprehending customer behavior in the fresh produce sector.